Anti‐inflammatory effects of polyphenols in arthritis. (9th October 2017) - Oliviero, Francesca; Scanu, Anna; Zamudio‐Cuevas, Yessica; Punzi, Leonardo; Spinella, Paolo
Abstract: Polyphenols have been extensively investigated with regard to their antioxidant, anti‐inflammatory, and immunomodulant properties in many inflammatory chronic conditions. The aim of this review is to summarise how these compounds can modulate the inflammatory pathways which characterise the most prevalent arthropathies including osteoarthritis, rheumatoid arthritis and crystal‐induced arthritis. Among polyphenols, epigallocatechin gallate, carnosol, hydroxytyrosol, curcumin, resveratrol, kaempferol and genistein have been the most widely investigated in arthritis. The most important results of the studies outlined in this article show how polyphenolic compounds are able to inhibit the expression and the release of a number of pro‐inflammatory mediators and proteolytic enzymes, the activity of different transcriptional factors and the production of reactive oxygen species in vitro. Studies on animal models of rheumatoid arthritis, osteoarthritis and gout show interesting results in terms of reduced tissue damage, restored cartilage homeostasis, and decreased levels of uric acid, respectively. Despite the multiple protective effects of polyphenols, there are no dietary recommendations for patients affected by rheumatic diseases. Future studies, including intervention trials, should be conducted to determine the relevance of polyphenols consumption or supplementation in arthritis. © 2017 Society of Chemical Industry